Epidemiology of Maxillo-Facial Trauma During COVID-19 Lockdown: Reports From the Hub Trauma Center in Milan. Issue 4 (December 2021) - Canzi, Gabriele; De Ponti, Elena; Corradi, Federica; Bini, Roberto; Novelli, Giorgio; Bozzetti, Alberto; Sozzi, Davide
Study Design: Retrospective study. Objective: Following SARS-CoV-2 pandemic break-out a lockdown period for the population and a reorganization of the Health System were needed. Hub -function Centers for time-dependent diseases were identified and Niguarda Hospital (Milan) was selected as main Regional Trauma Center. The purpose of our study is to report the experience of Niguarda Maxillofacial Trauma Team during this period, pointing out epidemiological changes in the presentation of trauma in comparison to the previous 3 years. Methods: Two hundred and sixteen patients were admitted to the Emergency Department from 8th March 2020 to 8th May 2020. One hundred and eighty-one had a diagnosis of Major Trauma and 36 had also facial fractures; 35 patients had isolated facial fractures. Data were compared to the activity during the same period in 2017-2019 and statistical analysis was carried out concerning demographic and clinical characteristics, trauma dynamics and positivity to COVID-19. Results: Cumulative curves of patients admitted because of Major Trauma describe a superimposable linear trend in years 2017-2019, while 2020 shows an increase from April 16th. Average age and number of more severe patients were higher than previous years. Epidemiological changes concerned road accidents, accidents involving pedestrians and cyclists, interpersonal violence, suicide attempts and domestic accidents. The incidence of facial fractures was confirmed through years and, according to its measured severity, 75% of patients required management. COVID-19 positivity without systemic symptoms didn't influence the type of treatment. Conclusion: The COVID-19 lockdown offers a unique opportunity to study the reversal epidemiological effects on trauma.